The Magnitude and Predictors of Overeducation and Overskilling in Latin America: Evidence from PIAAC - Juan Francisco Castro; Lorena Ortega; Gustavo Yamada; David Mata (Institute of Labor Economics (IZA), 2022)
Occupational mismatch, defined as a discrepancy between workers' qualifications or skills and those required by their job, is a highly debated phenomenon in developed countries, but rarely addressed in developing economies from a comparative perspective. This study investigates the magnitudes of overeducation and overskilling, and their correlates, in four developing Latin American countries that have undergone a rapid and unregulated expansion of tertiary education participation (i.e. Chile, Ecuador, Mexico and Peru). Using a variety of measures derived from PIAAC data, we find that the magnitudes of subjective overeducation, and objective and subjective overskilling are sizable (particularly in Chile and Mexico), albeit lower than OECD estimates. Differences in objective overskilling between the OECD and LAC countries are largely explained by workforce skill levels. We also find that overeducation, overskilling and credential inflation affect those occupations which arguably require less qualifications. Potential supply and demand side explanations for these patterns are discussed.
Keywords: O54; I26; J24; 330; Latin America; PIAAC; occupational mismatch; overeducation; overqualification; overschooling; overskilling